Preliminary Study Of Self-Setting 45S5 Bioglass Granular Cement - Imbau, Arnold (Universiti Sains Malaysia, 2022)
The objectives of this study is to investigate the effect of different concentration ofacidic calcium phosphate solution and soaking time on the 45S5 bioglass granular cement. The acidic calcium phosphate solution contain different concentration of MCPM (25 mmol/L, 50 mmol/L, 75 mmol/L and 100mmol/L) were imposed to 45S5 bioglass granules at temperature of 25°C (for 2, 4, 6 and 8 hours) to see its setting ability. Several characterization methods such as XRD, SEM, FTIR, measurement of pH value and compression test were carried out on 45S5 bioglass granular cement in order to understand its setting properties. XRD and SEM analysis result showed that the DCPD crystal are present and bridging to each other between the surface of 45S5 bioglass granular cement. The DCPD crystal that are form were increased when the concentration of acidic calcium phosphate is increased. Moreover, this study also shows the pH value of 45S5 bioglass granular cement that has been soak for 8 hours with acidic calcium phosphate solution are low after the specimen are immersed into HBSS solution for 1 day. On the other hand, this study also shows the compression strength for the specimen that are fully set at 8 hours of soaking time with acidic calcium phosphate solution with concentration of MCPM 100 mmol/L is 0.116 Mpa. Therefore, this study proved that the effect of concentration acidic calcium phosphate solution and the soaking time able to set the 45S5 bioglass granular at temperature 25°C.